An alternate approach to ensemble ENSO forecast spread: Application to the 2014 forecast. Issue 21 (6th November 2015) - Larson, Sarah M.; Kirtman, Ben P.
Abstract: Evaluating the 2014 El Niño forecast as a "bust" may be tapping into a bigger issue, namely that forecast "overconfidence" from single‐model ensembles could affect the retrospective assessment of El Niño–Southern Oscillation (ENSO) predictions. The present study proposes a new approach to quantifying an "expected" spread and uncertainty from noise‐driven processes and supplementing these measures with actual ENSO forecasts. Expanding on a previously developed coupled model framework that isolates noise‐driven ENSO‐like errors, an experimental design is implemented to generate an expected December Niño‐3.4 spread from March initial condition sea surface temperature errors that have similar structure to the 2014 and 2015 observed. Results reveal that the 2014 ENSO forecast falls within the expected uncertainty generated by ENSO‐independent, forecast‐independent, noise‐driven errors. Key Points: An alternate approach to quantifying ensemble ENSO forecast spread is presented The 2014 El Nino forecast falls within the expected spread from noise‐driven processes